Methodologies and applications of computational statistics for machine intelligence - Samanta, Debabrata 1987-; Althar, Raghavendra Rao 1981-; Pramanik, Sabyasachi 1978-; Dutta, Soumi 1986- (IGI Global, Publisher of Timely Knowledge, 2021)
"This book delves into computational statistics that focus on devising an efficient methodology to obtain quantitative solutions for problems that are devised quantitatively and brings together computational capability and statistical advanced thought processes to solve some of the problems encountered in the field" - Provided by publisher
Includes bibliographical references and index
Keywords: Machine learning; Statistical methods; fast; Machine learning -- Statistical methods; Aufsatzsammlung